2016
DOI: 10.1108/k-07-2015-0172
|View full text |Cite
|
Sign up to set email alerts
|

Offering a hybrid approach of data mining to predict the customer churn based on bagging and boosting methods

Abstract: Purpose – Churn management is a fundamental process in firms to keep their customers. Therefore, predicting the customer’s churn is essential to facilitate such processes. The literature has introduced data mining approaches for this purpose. On the other hand, results indicate that performance of classification models increases by combining two or more techniques. The purpose of this paper is to propose a combined model based on clustering and ensemble classifiers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 26 publications
(38 reference statements)
0
20
0
Order By: Relevance
“…In this study, the authors focus on tablet commerce in Nigeria context and not Africa nor globally, but the proposed framework can be adopted in other countries due to rapid diffusion of tablet device. The study employed quantitative method with structural equation modelling but the future researchers should look into the connectedness of a secured online shopping platform with security, trust, and ease of use using a mixed methodology (Ozturk et al 2016, Pappas 2016, Fathian, Hoseinpoor and Minaei-Bidgoli 2016. This mixed-methodology will enrich the study and pave the way for theoretical parsimony.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…In this study, the authors focus on tablet commerce in Nigeria context and not Africa nor globally, but the proposed framework can be adopted in other countries due to rapid diffusion of tablet device. The study employed quantitative method with structural equation modelling but the future researchers should look into the connectedness of a secured online shopping platform with security, trust, and ease of use using a mixed methodology (Ozturk et al 2016, Pappas 2016, Fathian, Hoseinpoor and Minaei-Bidgoli 2016. This mixed-methodology will enrich the study and pave the way for theoretical parsimony.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…It is complex for implementation but it is a benchmark for random forecast [1, 18, 19, 20, and 21]. Both types of classifiers: single and ensemble have been used for churn dataset classification [22] and it was found that selforganizing map, Principal Component Analysis, and Heterogeneous Boosting outperform other classification methods. A study based on the text of customers for the consideration of their positive and negative influences is presented for churn analysis on a macro level but not on an individual level [23].…”
Section: Related Workmentioning
confidence: 99%
“…There is no single hybrid approach instead multiple hybrid approaches are used to find more accurate results [28]. Available work in literature is based on a single data mining techniques; classification or clustering for the prediction of customer churn and mining of retention data of customer [9,22], however, some studies have been conducted which apply more than one technology [2,30].…”
Section: Related Workmentioning
confidence: 99%
“…Carver et al [13] empirically demonstrated that XGBoostbased prediction model outperforms logistic regression, the SVM and random forest model, and the prediction performance can be further improved after incorporating social network variables. Focusing on customer behavior, Fathian et al [14] set up a decision tree model with three feature attributes, i.e. recency, frequency and monetary value in the past half a year, and successfully predicted 90% of the customer churn with the model.…”
Section: Literature Reviewmentioning
confidence: 99%